Inventing God's law how the covenant code of the Bible used and revised the laws of Hammurabi - Wright, David P. 1953- (New York Oxford Oxford University Press, 2009)
David Wright argues that the so-called Covenant Collection of the Torah (Exodus 20:23-23:19) is chiefly the work of a single author, is the result of intellectual interaction with the author's sources & it may have had a politically ideological purpose, somewhat similar to that of the Laws of Hammurabi
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Code of Hammurabi; Bible -- Extra-canonical parallels; Law, Ancient -- Sources; Law -- Middle East -- Sources; Bible ; O.T ; Exodus XX, 23-XXIII, 19 ; Criticism, interpretation, etc; Code of Hammurabi; Bible ; O.T ; Extra-canonical parallels; Law, Ancient ; Sources; Law ; Middle East ; Sources; Kommentar